Experimental investigation of cooling performance of a CO2 heat pump system with an integrated accumulator heat exchanger for electric vehicles: Impact of refrigerant charge and valve opening. (April 2023) - Li, Gang; Tang, Zuohang; Zou, Huiming; Zhang, Rongrong
Abstract: The electric vehicle is drawing particular attentions due to the ever-increasing awareness of environmental pollution protection. For the environmental friendly CO2 automotive heat pump system, the investigation of refrigerant charge amount and valve opening on the system and component performance is still limited, especially for a system with an integrated accumulator heat exchanger. In addition, there is still a lack of oil circulation rate investigation on a CO2 vehicle system. In this study, an experimental investigation of refrigerant charge amount and valve opening for system/component performance and oil circulation performance has been systematically conducted for a cooling mode. There exists an optimal refrigerant charge amount corresponding to a maximum value of the system coefficient of performance, with an optimal charge value of 550 g for the electronic expansion valve opening from 30% to 50%, and with 500 g for the opening above 50%. Lifting the refrigerant charge amount from 450 g to 700 g for each valve opening provides a fall of ~35 °C for the discharge temperature and a growth of ~20 bar for the discharge pressure, respectively, and more pronounced at the low valve opening domains. Increasing the valve opening can accelerate the compressor efficiency, but the impact of the refrigerant charge amount may not carefully follow a similar trend. Lifting the refrigerant charge amount can lead to a significant rise in oil circulation rate, especially under high valve opening domains with the exception of 600 g charge level. Under the low refrigerant charge level, the low-pressure accumulator inlet port is the superheated state, and the oil circulation rate tends to be dropped with the increase of valve opening; while under the high charge level with the inlet to be two-phase state, the oil circulation rate curve behaves as a growing trend. This study is beneficial for the engineering community to have a deep understanding on the electric vehicle system thermal management to maintain the vehicle reliability, and provide safety and comfort benefits. Highlights: The optimal refrigerant charge is 550 g for the valve opening range from 30% to 50%. Refrigerant charge lift from 450 g to 700 g provides a fall of ~35 °C for discharge temperature. Increasing the valve opening can improve the compressor efficiency. Refrigerant charge lift offers a rise in oil circulation rate, more pronounced for high valve opening domains. For insufficient charge level, the oil circulation rate tends to be dropped as valve opening increases.